2011
DOI: 10.1002/jcp.22522
|View full text |Cite
|
Sign up to set email alerts
|

Activation of AMP-activated protein kinase is involved in vincristine-induced cell apoptosis in B16 melanoma cell

Abstract: The molecular basis for induction of apoptosis in melanoma cells by vincristine remains unknown. Here we tested the potential involvement of AMP-activated protein kinase (AMPK) in this process. We found for the first time that vincristine induces AMPK activation (AMPKα, Thr 172) and Acetyl-CoA carboxylase (ACC, Ser 79) (a downstream molecular target of AMPK) phosphorylation in cultured melanoma cells in vitro. Reactive oxygen species (ROS) dependent LKB1 activation serves as the upstream signal for AMPK activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(67 citation statements)
references
References 50 publications
4
63
0
Order By: Relevance
“…Detailed procedures can be found in other studies. 37,38 Briefly, the cells were lysed and the cell lysates were overlaid and incubated in microtiter plate modules coated with anti-Histone antibody. Samples were then incubated with anti-DNA peroxidase followed by color development with ABTS substrate.…”
Section: Caspase-3 Activity Assaymentioning
confidence: 99%
“…Detailed procedures can be found in other studies. 37,38 Briefly, the cells were lysed and the cell lysates were overlaid and incubated in microtiter plate modules coated with anti-Histone antibody. Samples were then incubated with anti-DNA peroxidase followed by color development with ABTS substrate.…”
Section: Caspase-3 Activity Assaymentioning
confidence: 99%
“…Two isoforms are known for catalytic subunit (a1, a2) and they are encoded by different genes (20). Recently, some studies have shown that AMPK plays critical regulatory roles in cancer cell growth and tumorigenesis of cancer cell (21)(22)(23). For example, some research showed that activation of AMPKa1 suppressed the growth of human colon cancer cell (24), whereas some other research showed that AMPKa1 could increases chondrosarcoma cancer cell migration (25), which indicated that AMPKa1 was controversial in different cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…AMPK can activate p53 by phosphorylating p53-Ser15 to induce cell cycle arrest and apoptosis (28,29). For example, a combined treatment with metformin and 2-deoxyguanosine, as well as vincristine, an anticancer agent, induced apoptosis in prostate and melanoma cells, respectively, by activating AMPK (30,31). Contrary to these reports, AMPK inhibition resulted in the sensitization of cancer cells to apoptosis by anticancer drugs such as cisplatin as well as metabolic stress such as hypoxia (32,33).…”
Section: Discussionmentioning
confidence: 99%